PERKEMBANGAN DAERAH PARIWISATA SANUR - Desak Made Sukma Widiyani (Universitas Dwijendra, 2014)
Sanur is one of Bali's tourism icon that has been known since 80 years ago. along with the increase of tourism development, in 1957 was built the first hotel in Sanur Village named Sindhu Beach Hotel, then continued with the construction of Bali Beach Hotel which began operating in 1966.Judging from the location theory, Sanur Tourism Regional development can be seen through the Growth Pole theory proposed by Perroux. Perroux's theory is based on the theory of innovation created by Shcumpeter, which focuses on the role of innovation (entrepreneurship) in increasing the growth/economic development.The purpose of this research to know and understand the meaning of Growth Pole Theory and aspects that surrounded it. The other purpose of this research is to find out more Sanur tourism area development until the present, and to know and understand the development of tourist areas of Sanur in terms of location theory Growth Center of Perroux.Keywords: Tourism, Sanur Village, Growth Pole, Development